An inclusive university environment in the Czech Republic based on the example of good practice at the University of Pardubice - Ilona Datko; Izabela Kochan; Jaroslav Myslivec; Zdenka Šándorová (Studia z Teorii Wychowania)
The ability of a society to utilise the creative human potential of all its members, including those with disabilities, is an important indicator of the development of society and the economy and the level of education, quality and performance of the education system. Our professional article enriches the current issue of inclusive education and inclusive special pedagogy in the Czech Republic (CR) with a description of the qualities of an inclusive university environment. The aim of the paper is to introduce the reader to the inclusive university environment in the Czech Republic using the example of good practice at the University of Pardubice.The following methodological approaches were used in the preparation of this article: a) a content analysis of legislation, strategic documents currently in force in the Czech Republic and available professional sources; b) quantitative design in the preparation of statistical overviews = the number of students with specific needs (SN) at the University of Pardubice (UPa) in 2012–2020 and financing the increased costs of study for students with specific needs at UPa in 2012–2020.